A missense mutation in Large Grain Size 1 increases grain size and enhances cold tolerance in rice - Chen, Xiaolong (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.